Inmates' empathy in relation to perceived parenting and attachment working models. Issue 4 (28th September 2017) - Lin, Hung-Chu; Yang, Yang; McFatter, Robert; Biggar, Raymond W.; Perkins, Rick
Abstract : Purpose: The purpose of this paper is to examine criminal offenders' dispositional empathy and relate it to perceived parenting characteristics of primary caregivers (measured as care and overprotection) and inmates' internal working models of the self and others (measured as attachment anxiety and avoidance, respectively). Design/methodology/approach: Compared to a group of 110 college students, the group of 102 inmates indicated lower levels of cognitive and emotional empathy (measured as perspective taking (PT) and empathic concern (EC), respectively). Among inmates, perceived parental care was related to PT; parental overprotection was related to EC. Findings: The inmates' data fit a model suggesting a mediational role of attachment anxiety in the relation between perceived parental overprotection and EC. Also, inmates' attachment avoidance moderated the relation between attachment anxiety and EC, so that the relation only occurred when attachment avoidance was not high. The findings suggested potential protective roles of early parental bonding and positive views of social others in enhancing empathy for justice-involved populations. Originality/value: The findings shed light on how inmates' perception of parenting related to both aspects of empathy and how cognitive representations of the self and others potentially underlie the association between perceived parenting and their disposition for EC. To cultivate dispositional empathy as a means of preventing delinquency, it is important to advocate not only parenting characterized as caring and warm, but also cognitive interventions on framing positive working models of social others, particularly for those who perceive their primary caregivers as overprotective and are highly avoidant to social closeness.